Development of a clickable activity-based protein profiling (ABPP) probe for agmatine deiminases. Issue 9 (1st May 2015) - Marchenko, Mikhail; Thomson, Andrew; Ellis, Terri N.; Knuckley, Bryan; Causey, Corey P.
Graphical abstract: Abstract: Agmatine deiminases (AgDs) catalyze the hydrolytic conversion of agmatine (decarboxylated arginine) to N -carbamoylputrescine with concomitant release of ammonia. These enzymes, which are encoded by some pathogenic bacterial species, confer a competitive survival advantage by virtue of energy production and acid tolerance through agmatine catabolism. Herein we report the development of a clickable activity-based protein profiling (ABPP) probe that targets the AgD encoded by Streptococcus mutans with high selectivity and sensitivity.